Comparison of trapping and camera survey methods for determining presence of allegheny woodrats. (17th December 2013) - Castleberry, Steven B.; Mengak, Michael T.; Menken, Theron E.
ABSTRACT Declines in Allegheny woodrat (Neotoma magister) distribution and numbers have been documented in the northern and western portions of the range for >30 years. Population trends in other parts of the range are uncertain, largely due to a lack of, or inconsistent, survey effort. We examined the efficacy of the trapping protocol currently used by many state and federal agencies for determining presence or absence of Allegheny woodrats at 17 study sites in western Virginia, USA. We compared trapping results with a remote camera methodology to determine whether remote cameras provide an effective alternative to trapping. We found that detection probabilities were high after 2 survey nights for both the trapping (0.86 ± 0.06) and camera (0.97 ± 0.03) methodologies. Percent of sites with documented woodrat presence after 2 nights was 88% and 94% for traps and cameras, respectively. We conclude that both methods are adequate for determining presence or absence of Allegheny woodrats and that each method has distinct advantages depending on the objectives. © 2013 The Wildlife Society.